Absensi Dosen pada Kegiatan Belajar Mengajar dengan Menggunakan QR Code Di Gedung AH Prodi JTD Politeknik Negeri Malang - Debby Gutama; Mochammad Junus; Putri Elfa Mas’udia (Politeknik Negeri Malang, 2021)
Education today demands a better regular and scheduled level of discipline so that the teaching and learning process can take place according to a predetermined schedule. However, most education parties still experience difficulties in demanding this because attendance activities are still manual and less regular in monitoring.The purpose of this study is to assist lecturers in carrying out daily class attendance by utilizing QR Code as a differentiator, which makes it easier for them to use smartphones from each lecturer.In this research, a lecturer attendance application using QR-Code was made where lecturers can do attendance using a smartphone camera for scanning the QR-Code that has been provided in each classroom.From the results of tests carried out on the application made, it was found that the application runs smoothly on several versions of Android and smartphone brands but on Android version 6.0 there is a lack of appearance and when scanning QRCode it takes time. When testing QoS, the highest delay value is in the 2nd Floor AH Building with a value of 120.1695 which means good and the average packet loss is 8%, while for the highest throughput on the 2nd floor AH Building with an average value of 7.598487 which means speed good network.